British Muslim men, stigma and clothing choices - Rajina, Fatima (The Palgrave handbook of gendered Islamophobia, 2024)
This chapter examines the changing perceptions of dress, focusing on the lungi, funjabi (The funjabi, also known as panjabi, is a kurta-like top, a loose shirt, over a pair of trousers of sometimes it is worn over a lungi; a lungi is a sarong worn by men around the waist and just above the ankle, it is usually made of cotton, and a thobe is an ankle-length, long-sleeved and robe-like garment worn primarily by men in the Arabian Peninsula) and the thobe, amongst the British Bangladeshi Muslim male diaspora in the East End of London. Through various historical trajectories, I argue that the research participants in this chapter dress their bodies according to the current meanings attributed to the garments. These meanings are (re)-configured using a meta-constructed stigma guideline they interpret using their faith, Islam, and the wider dominant discourse around acceptability and respectability. Drawing on in-depth interviews with British Bangladeshi Muslims in East London in the UK, I demonstrate how the ubiquitous presence of the Islamophobia arc, invisible yet dictating behaviours and responses in the every day, along with the heightened political scrutiny of British Muslims, and the internalising of anti-Muslim racism have intensified clear demarcations of what constitutes religious and/or ethnic dress. To extrapolate the continuous interplay in constructing a British Bangladeshi Muslim male identity via clothing, I explore this as paradigmatic of how stigma is located consequently determining men’s sartorial choices. The chapter ends with considering how the socio-positioning qua the political landscape facilitates a structural restriction that trickles down to individual’s choices in what the appropriate Muslim male body can look like in the public sphere.